Pengaruh Muscle Energy Tehnique (Met) Dan Dynamic Stretching Terhadap Fleksibilitas Otot Hamstring Pada Pemain Futsal - Mufidati, Banik Hasniar, Arif Pristanto, S.Fis., M.Fis (2017)
Background: a futsal player with flexibility muscles hamstring better able to help increase during play futsal performance .To increase the flexibility muscles hamstring can be done by exercise MET and dynamic stretching. Based on pre study to the futsal players in Sragen , that exercise never done before and only an exercise dynamic stretching Objective : toknow comparison stretching method happy and stretching dynamic to flexibility muscle hamstring on a player futsal in sragen Method: research methodology use quasi experiment , with pre and post test two group design. Sample as many as 24 futsal player with using total sampling. Research instruments met by the exercise and dynamic stretching to calculate flexibility hamstring muscle .Data analysis using wilcoxon test and mann whitney The average flexibility muscle hamstring pre test MET group was 46,25 ±4,820 and post test = 55, ± 5,410 . Pre test group dynamic stretching was 47,08 ±5,820 and post test 55,83 ± 4,170 .Wilcoxon test results p = 0,007 .The results of the dynamic stretching wilcoxon obtained value p = 0,003 .Test different the influence of flexibility muscle hamstring between dynamic stretching p = 0,977 . Conclusion: there is the influence of muscle energy technique to flexibility muscle hamstring on a player futsal. There is influence of dynamic stretching to flexibility muscle hamstring on a player futsal. There is no difference influence of between MET and dynamic stretching to flexibility muscle hamstring on futsal player.